Explaining transhumance-related violence: Fulani Ethnic Militia in rural Nigeria. (January 2022) - George, Justin; Adelaja, Adesoji; Vaughan, Olufemi; Awokuse, Titus
Abstract: The growing incidence of farmer-herder conflicts in Sub-Saharan Africa raises questions about its underlying causes. In Nigeria, for example, where both terrorism and farmer-herder conflicts have increased, questions arise about the roles of Boko Haram, vis-à-vis climate, natural disaster, grazing resources, market and policy-related constraints to grazing. To explain the causes of transhumance-related violence, we conceptualize push factors, which increase the spread of pastoral activities away from historical grazing areas; pull factors, which attract pastoralists to previously less-grazed areas; and escalating factors which explain increased pastoral violence in the latter. We further develop a theoretical location choice model to explain the grazing location decisions of herdsmen and violence resulting from resistance from destination communities. Using the Nigerian Fulani Herdsmen situation as a case study, we confirm the expected influences of hypothesized resource-related causal factors and the escalating roles of some economic, policy, market and land use challenges. Specifically, we empirically find that Boko Haram attacks escalate farmer-herder conflicts by intensifying the effects of drought, natural disasters, high temperature and other grazing constraints on herdsmen. We also explore possible policy solutions to the growing human casualty from violent attacks. Highlights: We investigate the factors leading to farmer-herder conflicts and related violence in rural Nigeria. We conceptualize push, pull and escalating factors which explain the farmer-herder crisis. Spatial grid level panel data analysis is used to explore the roles of hypothesized factors. We empirically confirm the role of Boko haram attacks and various climate related factors. We highlight the complexity of this conflict type and the need for evidence-based solutions.